Hubungan Usia Menarche dengan Kejadian Kanker Payudara pada Wanita Dewasa - Balgahoom, Najwa; Surjadi, Lily Marliany; Kurniawan, Febriyanto (Jurnal Biomedika dan Kesehatan, 2025)
Background Breast cancer is a non-communicable disease that is a health problem worldwide. Based on breast cancer prevalence data according to the World Health Organization (WHO) in 2020, 2.3 million women have been diagnosed, and 685,000 of them have died from breast cancer. Several factors can increase the risk of possible breast cancer incidence, some of which are age of menarche, nulliparity (never giving birth), and obesity. The purpose of this study was to determine the relationship between age at menarche, body mass index (BMI), and nulliparity with the incidence of breast cancer in adult women. Methods This cross-sectional study was conducted at Dharmais Cancer Hospital, Jakarta, with 104 respondents aged 19-59 years with breast complaints during March-May 2024. By excluding respondents with consecutive non-random sampling techniques. Data analysis using the Mann-Whitney test with a probability level (p < 0.05). Results The data showed that 98 respondents had breast cancer, and over 80% of them had the no special type (NST) breast cancer. Meanwhile, 6 respondents were not diagnosed with breast cancer. There were 62 respondents with normal menarche age (>12 years), with a p-value of 0.979. Additionally, 91 respondents had multiparity, with a p-value of 0.891. Furthermore, 74 respondents had an excessive body mass index (BMI), with a p-value of 0.336. Conclusions Based on statistical analysis, it can be concluded that there is no significant relationship between menarche age, body mass index (BMI), and parity with breast cancer in adult women.